Assessment of quality service in the marketing of fruit and vegetables in retail formats in Brazil - Scalco, A. R. [UNESP]; Oliveira, S. C. [UNESP]; Fonseca, A. C. [UNESP]; Rodrigues, F. M. [UNESP] (My University, 2011)
Fresh produce are distributed by various retail formats such as supermarkets, street fairs, retail shops, and grocery stores. The purchase of these products by consumers depends on numerous factors such as satisfaction with the service, product quality, facilities, cleanliness and hygiene of the place, proximity, among other factors. Thus, this research aims to perform an evaluation of the quality of the services in street markets and section of fruit and vegetables (FV) in supermarkets in the city of Tupa, to point out the strengths and weaknesses of these marketing channels and propose possible improvements. The study found the quality of services in both retail facilities to be bad, highlighting the dimensions of tangibility and reliability.
Keywords: Fruit and vegetables; Retail formats; Service quality; Street markets; Supermarkets